Perubahan Nilai Fe3+ dengan Pemberian Zeolit pada Tanah Sulfat Masam Pasang Surut - Putra, Wira Megantara; Nurlaila, Nurlaila; Santoso, Untung (Universitas Lambung Mangkurat, 2025)
Acid sulfate soils are usually found in lowland areas with flat topography around coasts or large rivers influenced by tidal waters. These soils are prone to periodic flooding and drought due to very acidic conditions and frequent waterlogging, resulting in low fertility. The causes of infertility in acid sulfate soils are low nutrient levels and high levels of toxic elements. Zeolite can be a solution because it increases soil fertility, reduces toxic compounds, raises pH, improves soil structure, and has high base saturation. Additionally, zeolite can reduce Al and Fe content in wetland soils. This research aims to determine the degradation of Fe values by administering sulfate soil zeolite during high tide periods.The study was conducted from April 2023 to August 2023 at the Integrated Agroecotechnology Laboratory and the Agricultural Swamp Land Standardization Testing Instrument Laboratory. This research uses a qualitative test method, employing a systematic literature review to determine the effect of zeolite incubation duration on Fe content and pH in tidal acid sulfate soils. The results showed that there was a change in the Fe3+ value by administering zeolite in the Z3 treatment with a dose of 11 tons ha-1 with Fe3+ results of 196.15 ppm and was able to reduce Fe levels in acid sulfate soil and the Z3 pH obtained was 3.41, there was a very small increase.